5PSQ-135 Adequacy of hypolipemiant treatment in primary healthcare. (14th March 2021) - Salom, C; Campabadal, C; Bejarano, F; Marco, N; Castillo, L; Conde, S; Marcos, Á; Roch, MÁ; Sanjuan, A; Canadell, L
Abstract : Background and importance: Based on the criteria lipid lowering efficacy, safety, experience of use and cost, the statins simvastatin, pravastatin and ≥40 mg atorvastatin, and gemfibrozil fibrate, are prioritised in our territory. Aim and objectives: To optimise lipid lowering treatment in primary healthcare (PH) patients. Material and methods: A prospective study (June to July 2020) was carried out in a PH centre, with data obtained from the ECAP computerised medical record. Patients on lipid lowering treatment not considered firstline were included. Data were collected for demographic variables (age and sex), patient adherence and therapeutic effectiveness, drugs involved and interventions (proposal, acceptance and implementation). The prescription was validated by the pharmacist and the interventions were proposed to the physician. Results: 300 patients were included, aged 68 (11.4) years (157 (52.3%) men), assigned to eight physicians. 44 (14.7%) patients were not adherent, and the therapeutic objective was not reached in 62 (20.7%) patients. 296 (86.5%) interventions were suggested on 342 active principles: change in therapeutic equivalent, 29.4%; intensify the dosage, 27.3%; interrupt the drug, 24.7%; reassess the indication, 9.8%; change the active principle, 7.1%; and reduce the dosage, 1.7%. Interventions involved: atorvastatin, 38.7%; rosuvastatin, 17.7%; fenofibrate, 16.3%; ezetimibe, 15.9%; pitavastatin, 9.2%; lovastatin, 1.1%; and fluvastatin, 1.1%. The final drugs were: atorvastatin, 54.3%; simvastatin, 34.7%; gemfibrozil, 7.5%; and pravastatin, 3.5%. Physicians accepted 289 (97.6%) interventions. At the 2–3 month follow-up, the implementation carried out lowered the percentage of drugs not considered firstline from 27.49% to 22.07% (19.71% reduction). Conclusion and relevance: The prescription of hypolipemiant drugs was not in accordance with the recommended standards, possibly due to ignorance of institutional recommendations, magnification in the perception of adverse effects of classic treatments and therapeutic inertia. Review of the prescriptions by the specialist pharmacist was an added value in optimising the treatment of these patients by means of a multidisciplinary team. It will be interesting to analyse the results at the 1 year follow-up when all patients should have received a visit: the changes implemented, control of the lipid profile after the intervention as well as the savings in drug costs. References and/or acknowledgements: Conflict of interest: No conflict of interest